Interrelated Complexities in The Arabic Structural Reposition: Layers of Deviation, Relation, and Implication - Khitam, Achmad Khusnul (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
Abstract: This article mainly discusses the case of structural reposition in the Arabic language and the interrelated complexities occur within the case. Technically, the case of structural reposition, to some extent, is closely similar to the terms of at-taqdīm wa at-ta’khīr in Arabic linguistic tradition. Several studies as well as researches concerning this issue have been done, mainly to describe structural elements of this case. There are mainly three elements that this article focusses on: linguistic style (deviation), linguistic structure (relation), and the implied meaning (implication). The result of this article shows that there are at least three linguistic elements (style, structure, and meaning) occur within the case of structural reposition. Those three elements have a close interrelated function that operate simultaneously (mutazāmin wa mutaẓāfir) in each linguistic unit within the case. In this sense, the structural reposition of linguistic units represents deviation, while the connection occurs between the existing units represents relation, whereas both deviation and relation can provide direct implication in producing certain meaning